¿Conceptos o procesos? - Salas Cabrera, H. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper discusses the characteristics and implications of Science Teaching, centered in the processes —that is, leading to the development of intellectual abilities— or in the concepts and adressed to the acquisition of an ensemble of knowledge.